Penggunaan Teknologi Informasi Pada Proses Rekapitulasi dalam Perspektif Pemilu Transparan di Kabupaten Asahan - Lingga, Roma Indah; Zulkarnain, Iskandar; Fauzan, Indra (Universitas Medan Area, 2024)
This research discusses the use of Sirekap as a publication and recapitulation tool in the 2024 Election to support the transparency of election results in Asahan Regency. The research objective is to explain how information technology in recapitulation by the KPU can support transparent elections and analyze the weaknesses of the recapitulation information system for improvement. Using International IDEA's Pyramid of Trust concept, this research is descriptive and qualitative with data collected through interviews, documentation, and observation. Informants consisted of various related parties, a total of 12 informants. Data analysis includes reduction, presentation, condensation, and conclusion drawing. The results show that information technology in recapitulation does not fully support transparent elections in Asahan and needs further evaluation. However, public awareness of the publication of vote results has increased. The use of Sirekap requires improvement in terms of human resources, network/server, data accuracy, and information integrity.